Synthesis and Characterization of Composite Starch/ Chitosan/ Sugarcane Fiber/ Zink Oxide (ZnO) Bioplastics - Azmi, Muhammad Afzan; Lee Woon Kiow (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Starch-based bioplastics, optimized with the right additives, could be effective for industrial use, supporting environmental sustainability by mitigating plastic pollution and reducing greenhouse gas emissions. The objective was to investigate the mechanical, thermal, and biodegradable properties of starch-based bioplastics by incorporating sugarcane bagasse fiber at varying concentrations (0.5%, 0.75%, and 1%). The bioplastics were produced using a casting method and analyzed through tensile, water solubility, water resistance, biodegradability tests, SEM, and FTIR analysis. Results revealed that the addition of sugarcane bagasse fiber significantly improved the tensile strength and biodegradability, with 1% fiber yielding the best overall performance. However, water resistance decreased with higher fiber content, highlighting a trade-off between mechanical and barrier properties. These findings demonstrate the potential of sugarcane bagasse fiber to enhance bioplastic performance, offering a sustainable solution to mitigate plastic pollution and reduce reliance on fossil fuel-based materials.